2021
DOI: 10.1186/s13046-021-01990-y
|View full text |Cite
|
Sign up to set email alerts
|

LINC00511 drives invasive behavior in hepatocellular carcinoma by regulating exosome secretion and invadopodia formation

Abstract: Background Tumor cells are known to release large numbers of exosomes containing active substances that participate in cancer progression. Abnormally expressed long noncoding RNAs (lncRNAs) have been confirmed to regulate multiple processes associated with tumor progression. However, the mechanism by which lncRNAs affect exosome secretion remains unclear. Methods The underlying mechanisms of long noncoding RNA LINC00511 (LINC00511) regulation of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…For example, LINC00511 may contribute to breast cancer tumorigenesis, proliferation, radioresistance, and stemness 20,21 . The tumor-promoting functions of LINC00511 have also been reported in gastric cancer 22,23 , hepatocellular carcinoma 24,25 , colorectal cancer 26, 27 and bladder cancer 28,29 . LINC01087 could represent a novel, speci c and promising biomarker not only for the diagnosis and prognosis of luminal subtypes and triple-negative breast cancers but also as a predictive biomarker of pharmacological interventions 30 .…”
Section: Discussionmentioning
confidence: 83%
“…For example, LINC00511 may contribute to breast cancer tumorigenesis, proliferation, radioresistance, and stemness 20,21 . The tumor-promoting functions of LINC00511 have also been reported in gastric cancer 22,23 , hepatocellular carcinoma 24,25 , colorectal cancer 26, 27 and bladder cancer 28,29 . LINC01087 could represent a novel, speci c and promising biomarker not only for the diagnosis and prognosis of luminal subtypes and triple-negative breast cancers but also as a predictive biomarker of pharmacological interventions 30 .…”
Section: Discussionmentioning
confidence: 83%
“…In addition to this, the silencing of LINC00511 expression suppressed cell viability, proliferation, migration, and invasion, and accelerated the apoptosis of glioma cells via a suggested miR-15a-5p/AEBP1 axis [ 36 ]. Other studies have associated LINC00511 with breast cancer [ 37 ], hepatocellular carcinoma [ 38 ], and bladder carcinoma [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“… 20 Research by Peng et al showed that the expression of LINC00511 was higher in HCC tissues, and the mechanism study revealed that the invasion pseudopodia and exosomal secretion induced by LINC00511 were involved in tumor progression. 21 Yin et al found that LINC01133 expression in HCC tissues was elevated, and can predict the poor prognosis of HCC patients; in‐vitro studies showed that overexpression of LINC01133 can promote the proliferation and aggressive phenotype of HCC cells, and promote tumor growth and lung metastasis in vivo, while knockdown LINC01133 had the opposite effect. 22 In addition, studies have also reported that lncRNA plays an important role in the chemotherapy resistance of HCC.…”
Section: Discussionmentioning
confidence: 99%